Non-Exenteration Management of Sino-Orbital Fungal Disease. Issue 6 (November 2017) - Athavale, Dnyaneshwar D.; Jones, Robin; O'Donnell, Brett A.; Forer, Martin; Biggs, Nigel
Abstract : Purpose: To describe the non-exenteration management of sino-orbital fungal infection, a life-threatening condition for which orbital exenteration is generally considered a first-line treatment. Methods: A retrospective case series is presented of 7 orbits in 6 consecutive patients admitted and treated at 2 major metropolitan tertiary teaching hospitals in Sydney, New South Wales, Australia. Results: Seven orbits in 6 consecutive patients with sino-orbital fungal infection were treated conservatively with surgical debridement and intravenous antifungal agents. Four patients were immunosuppressed and the other 2 patients were otherwise healthy. All presented with pain, proptosis, or loss of vision. Causative organisms found were Mucormycoses, Aspergillus, and Scedosporium prolificans . Exenteration was avoided in all patients as part of their planned management and 5 patients, including 1 with bilateral disease, survived their disease without exenteration. Medical treatment included intravenous liposomal amphotericin B or voriconazole. A single immunosuppressed patient deteriorated and as a last resort, exenteration was performed, but this made no difference to his clinical course and in retrospect could have been avoided as he died of multiple cerebral metastases diagnosed shortly after his deterioration. Conclusion: The authors recommend that patients with sino-orbital fungal disease preferably be treated conservatively, without orbital exenteration. Abstract : Sino-orbital fungal infection can be managed successfully with conservative surgical debridement and systemic antifungal agents without need for disfiguring operative interventions.